Mental Health of Surgical Center Nurses: an integrative review (Research, Society and Development, 2021)
Objective: to identify the scientific literature and factors that impact the mental health of nurses who attend surgery centers. Method: integrative review of literature searching for databases on Latin American Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE), Science Direct, Scopus and on Database on Sickness (BDENF). The studies were carried out during May 2021, referring to the period from January 2018 to May 2021. The studies were fully accomplished, and their content is available in Portuguese, English and Spanish. Results: 172 items have been obtained from search refinement and combination of descriptors. After removing 31 duplicated studies, 141 were selected as well as two abstracts and other titles; amongst them, 22 were chosen for comprehensive and critical reading. Three studies were elected to compose the review of the thematic analysis that emerged in the category: stressors in the environment of the surgical center. Conclusion: the factors identified as having an impact on the mental health of perioperative nurses were related to factors in the work environment, such as the poor interdisciplinary relationship between professionals, the organization, the structure and support for nurses. The study was limited to searches of studies published in the last three years, which may be related to the scarcity of publications on the subject, including national publications, representing the need for more studies on the topic of mental health in perioperative nursing.